Drawing - in and outside - writing - Chorpening, K.; Fortnum, R.; Morrens, P.; Nys, A. (Leuven Acco, 2012)
Drawing in and outside Writing is an in-depth study of the entanglement of drawing and writing produced by London based artists, Kelly Chorpening and Rebecca Fortnum and Belgian artists, Peter Morrens and Ans Nys during a year long collaboration. The project reflects on the blurring of the creative acts of drawing and writing, provoked by the artists working side by side. The research is driven by strategies of re-interpretation, re-staging, and reflecting on an others drawings and writings. The artists found it useful to consider an exchange of drawings as a visual conversation or 'correspondence. These research strategies opened up new ways of considering the relationship between drawing and writing, particularly how tracing and copying function in the quest for knowledge and understanding.